Finite element method in machine design - Ramamurti, V. (Viswanatha), 1938- (Oxford, U.K. : Alpha Science International, 2009)
Accompanying CD-ROM contains source codes asociated with the material presented both in C and FORTRAN languages.
Book is accompanied by 1 computer optical disc, entitled'Finite element method in machine design' bearing the same call number and available at Bahagian Koleks Media
Includes bibliographical references and index.
Accompanying CD-ROM system requirements: IBM PC or compatible; Windows; CD-ROM drive.
Keywords: Machine design; Finite element method